Guangsangon E triggers mitochondria dysfunction and mitophagy in triple‐negative breast cancer and leads to non‐apoptotic cell death. Issue 12 (19th September 2022) - Shen, Yuhang; Han, Zhuo; Wang, Luping; Liang, Yan; Zhang, Xiaoyong; Li, Wei; Li, Shouxin; Tian, Jingkui; Han, Haote
Abstract: Guangsangon E (GSE) is a natural product separated from Morus alba L. It has been reported to treat lung cancer through autophagy. However, whether GSE is effective in repressing triple‐negative breast cancer (TNBC) cells is yet to be elucidated. In the present study, GSE inhibited cell growth of MDA‐MB‐231, MDA‐MB‐453, and MDA‐MB‐468 cells. Moreover, GSE induced mitochondrial dysfunction, including membrane potential loss, mitochondria fission, and reactive oxygen species accumulation, and finally led to mitophagy‐related non‐apoptotic cell death. In the xenograft tumor nude mice, GSE treatment significantly reduced the size and weight of MDA‐MB‐231 tumors. The tumor inhibition rates of GSE treatment were 49.68% (low‐dose) and 48.73% (high‐dose). In summary, GSE is a potential anticancer drug available for treating TNBC with apoptosis resistance.